Fasting as a Complementary Approach in Cancer Care: RecentEvidence and Public Health Relevance - Almira Fahrinda; Anik Purwanti; Mutmainah Arif (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Cancer remains a leading cause of morbidity and mortality worldwide, including in Indonesia. Conventional therapies such as chemotherapy and radiotherapy often cause severe side effects that reduce quality of life. Nutritional strategies, particularly fasting and its variations— intermittent fasting, time-restricted eating, and fasting-mimicking diets—have gained attention as potential complementary approaches. Objective : This narrative review summarizes current evidence on fasting in cancer care, focusing on clinical outcomes, underlying biochemical mechanisms, and public health relevance in the Indonesian context. Research Methods/ Implementation Methods : Literature from 2020–2025 was reviewed using PubMed and Scopus. Included articles comprised systematic reviews, clinical trials, and pilot studies on fasting in cancer patients. Results : Intermittent fasting may improve metabolic parameters such as insulin sensitivity, blood glucose, and body weight, with possible benefits for fatigue and quality of life. Time-restricted eating is feasible and acceptable, though its impact on treatment outcomes remains unclear. Fasting- mimicking diets show promise in preclinical studies, but human trials are scarce. Cultural practices such as Ramadan fasting provide a natural model of daily fasting; however, its role in oncology has not been systematically evaluated. Conclusion/Lesson Learned : Fasting appears promising as a supportive intervention in cancer care, but evidence is still preliminary. Integration into public health strategies, including exploration of Ramadan fasting in Indonesia, requires further study through large-scale, culturally adapted trials.